EVA Faktor-Faktor Yang Mempengaruhi Keputusan Konsumen Memilih Menggunakan Jasa Go-Jek Online (Studi Kasus Pada Mahasiswa Universitas Islam Riau) - Eva Sundari; Deswarta Deswarta; Sabrizan Helmi (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
perception factors, service quality, corporate image, and word of mouth on consumer decisions to choose to use Go-Jek online services (Case Study of Riau Islamic University Students). Methods of Selection and Sampling were carried out using the Purposive Sampling technique, the Purposive Sampling technique, namely Taking Samples Deliberately in each of the Faculties at the Islamic University of Riau Using Go-Jek Services The number of samples taken as many as 100 students in several faculties at the Islamic University of Riau. This research data is analyzed by Multiple Linear Regression Analysis and processed using SPSS For Windows Version 20. Application. The results of this study state that Price Perception, Service Quality, Company Image, Word Of Mouth. Influence on Consumer Decisions to choose to use Go-Jek Online services.